The influence of Debt Equity Ratio (DER), Earning Per Share (EPS), and Price Earning Ratio (PER) on stock price - Rahmawati, Yustika; Hadian, H. Niki (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study aims to determine how the debt-to-equity ratio, earnings per share, price earning ratio, and stock prices are described in consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. Also, to determine the effect of partially and simultaneously debt to equity ratio, earnings per share, and price earning ratio on stock prices in consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. Research Methodology: The research method used in this study is an explanatory method. The research method used in this research is explanatory. The sampling technique used in this study is non-probability sampling with a purposive sampling method so that the sample size is 34 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2016-2018. The analysis method used in this research is panel data regression analysis using Eviews 9. Results: The results showed that the debt to equity ratio, earnings per share, and price earning ratio affected stock prices. Also, the research results show that the magnitude of the influence of the debt to equity ratio, earnings per share, and price earning ratio in contributing to the effect of stock prices is 98.7%. Limitations: The research is limited to just a few factors, namely debt to equity ratio, earnings per share, and price-earnings ratio to stock prices. Besides, this research is only limited to companies in the consumer goods industry that are listed on the Indonesia Stock Exchange for the period 2016-2018. Contribution: This research is expected to provide benefits for companies in increasing the company's share price in the capital market from several financial performance factors including debt to equity ratio, earnings per share, and price earning ratio.